ANALISIS KERJASAMA AKTOR-AKTOR NON PEMERINTAH DALAM PENINGKATAN SUMBER DAYA MANUSIA SEBAGAI INDIKATOR KEBERHASILAN PEMBANGUNAN PENDIDIKAN - Talakua, Jeane F.D.; Wiloso, Pamerdi Giri; Therik, Wilson M.A. (KRITIS, 2016)
The article describes the cooperation of non-governmental actors conducted by Christian High School 1 Salatiga and the Institute of Chinese Language Course "Sha Hua" by OCA (Overseas Chinese Affairs). This article is the beginning of a process of cooperation to the success achieved from the cooperation between Christian High School 1 Salatiga and the Institute of Chinese Language Course "Sha Hua" With OCA (Overseas Chinese Affairs) in the improvement of human resources as development indicators by displaying a different dimension. This article also describes the cooperation Christian High School 1 Salatiga and the Institute for Language Course Mandarin "Sha Hua" which embodies the development of education through scholarships, cooperation model performed by actors non-government (in this case Christian High School 1 Salatiga and the Institute for Language Course Mandarin "Sha Hua") to the role of education to national development. Perspective theory used to analyze the cooperation of non-governmental actors is the theory of globalization, international cooperation theory and the theory of social capital (social capital). The method used was a case study (case study). From the data analysis found that: First, cooperation between non-governmental actors is made up of trust fosters a strong commitment to the same goal, and it allows the understanding that has been formed is not easy to be stopped just because of interrelated to one another; Secondly, the State is a partner cooperation between non-governmental actors become the most important thing to consider in a partnership; and Third, education is very important role in human development.